Analisis Tingkat Kelelahan Mahasiswa Dalam Pembelajaran Daring Diera Pandemik Covid-19 Tahun Ajaran 2020/2021 - Ayly Soekanto; Emillia Devi Dwi Rianti (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2021)
The Covid-19 case is a global pandemic outbreak, resulting in the closure of the implementation of education carried out online by students as well as the work on the results of research data, based on filling out an implementation questionnaire with an average result related to effectiveness, there are 44% which shows that it is not good. Students experience fatigue by 56%, student concentration in lectures by 20%, internet use by 72%, indicating that the conversion value of the level of achievement and qualifications is sufficient, resulting in boredom and stress, as well as physical and mental fatigue. The learning process online or online is very important, supported by the need for internet access